Transformational changes in marketing services in the conditions of quarantine and war (Economics and region, 2023)
Marketing services are no longer new in the activity of Ukrainian enterprises. Their development has begun several decades ago and continues till today. In recent years, the composition of marketing services has finally been formed, they include: loyalty marketing, event marketing, sponsorship, consumer marketing band trade marketing. Until 2019, all components of marketing services in Ukraine had stable growth dynamics, but with the emergence of a global pandemic caused by the Covid-19 disease, this trend changed. The tendency for events, which was widely developed by 2019, has become difficult to maintain in quarantine conditions. Talking about such classic tools as consumer and trade marketing, they have not undergone significant changes, but they have increased in demand from advertisers due to their ability to generate additional value. Interest in loyalty marketing as a means of customer experience research continued to grow. The involvement increase of communication channels in communication with the consumer and creating a unique consumer experience should be highlighted among the trends. We investigated the changes that took place in marketing services both in Ukraine and around the world during 2019-2022. Services continued to evolve, adapting to new trends and challenges, becoming more important than ever to businesses as more people stayed at home and used online services to shop and get information. Effective marketing strategies and tools have become very important to attract and retain customers. The use of various digital channels to attract customers, such as social media, search engine optimization, e-mail and online advertising, have become even more popular. In Ukraine, the war had a strong impact on the advertising market: almost half of the active advertisers stopped their advertising activities. Internet advertising suffered smaller losses, almost two-thirds of companies continued to use this tool after 24 February 2022. Most companies focus on digital communication. In general, this is a demand for online retail research projects, e-commerce promotions, CRM and loyalty programs. The use redistribution of services mentioned in the article will maintain its trend in the future. In the system of modern economic, socio-political and epidemiological situation, enterprises increasingly need marketing support, where marketing services play an important role. The evolution of marketing services, Internet technologies and the trend of digitization continue to create new ways of communications for both small and large businesses.
Keywords: marketing services; marketing; digitalization; marketing tools; social networks